Diversidade de espécies de Aspergillus, Penicillium e Talaromyces identificadas por filogenia molecular e espectrometria de massas MALDI-TOF - Cardoso, Emanuelle Burgos (2015)
This study aimed to characterize and identify 124 strains of the genera Aspergillus, Penicillium and Talaromyces obtained in Brazil from substrates such as soil, marine sediment, litter, and seeds, which were deposited in the Coleção Micológica de Lavras - CML, Departamento de Fitopatologia, Universidade Federal de Lavras. Isolates were grown on MEA and CYA at 25°C in the dark. A set of 98 strains from the three genera was selected for MALDI-TOF analysis. Representative strains of groups defined by the dendrogram generated through the mass spectra were submitted to analysis of molecular phylogeny using sequences of the locus RPB2. Other 26 strains, not previously analyzed by MALDI-TOF, were identified directly by phylogeny with RPB2 sequences. The analysis of MALDI-TOF spectra distinguished 17 groups in Aspergillus, 16 in Penicillium and 10 groups in Talaromyces. Phylogenetic analysis, including ex-type sequences as reference, allowed for the identification of 20, 19, and 12 species of Aspergillus, Penicillium and Talaromyces, respectively. Both techniques employed provided congruent results, distinguishing 20 species in Aspergillus, 19 in Penicillium and 12 species in Talaromyces. The results confirm the utility of MALDI-TOF to distinguish species within the three genera. Thus, this technique serves as a tool for screening mycological collections and, combined with phylogeny, may be used for the identification of strains to validate spectral databases.